The The Influence of Solvent Volume on Raw Material and Cooking Time in the Delignification Process of Paper Making from Kepok Banana Peel Pulp - Kusyanto, Kusyanto (2477 - 6165, 2023)
The potential applications of paper made from kepok banana peel include greeting cards, book covers, and other art and craft projects. The use of kepok banana peel in papermaking adds a new dimension and unique artistic value to the field. Furthermore, it has a positive impact on the environment by reducing agricultural waste that would otherwise be discarded. The purpose of this study was to investigate the effect of the volume of NaOH solution on the mass of kepok banana peel and the ripening time needed to produce the best pulp according to SNI 7274:2008 and SNI 14-6519-2001 standards. The study involved testing different volumes of solvent, ranging from 300 mL to 700 mL, and conducting the delignification process for 60 to 120 minutes with 30-minute intervals. The resulting pulp was then utilized in the papermaking process. Based on the conducted study, the optimum operating conditions were achieved using a solvent volume of 500 mL for a duration of 90 minutes. The analysis revealed a cellulose content of 90.8%, lignin content of 5.02%, water content of 16.85%, and paper tear resistance of 444.584 mN.